PENGARUH MODEL KOOPERATIF TIPE TPS TERHADAP KETERAMPILAN MENULIS KARANGAN DESKRIPSI SISWA SMP - Saputri, Rosi Arnis; Basri, Irfani; Arief, Ermawati (Universitas Negeri Padang, 2016)
ABSTRACTÂ This research is aimed to describe the influence cooperative model type TPS concerning description essay writing skills of student class VIII SMP Negeri 1 Pariaman. The research method of this study is experiment method with quasi experiment. The results of this study there was significant influence cooperative model type TPS concerning description essay writing skills of student class VIII SMP Negeri 1 Pariaman at significant level 95% with degrees of freedomÂ (n1+n2)-2, namely ttable <tarithmetic (1,70<9,19). Ho was rejected and H1 was accepted because the results of the hypothesis test prove that value of ttable was smaller than tarithmetic.Â Kata kunci: pengaruh, kooperatif, TPS, karangan deskripsi